GRIN2A Variants Associated With Idiopathic Generalized Epilepsies - Liu, Xiao-Rong; Xu, Xing-Xing; Lin, Si-Mei; Fan, Cui-Ying; Ye, Ting-Ting; Tang, Bin; Shi, Yi-Wu; Su, Tao; Li, Bing-Mei; Yi, Yong-Hong; Luo, Jian-Hong; Liao, Wei-Ping (Frontiers in Molecular Neuroscience, 2021)
Objective: The objective of this study is to explore the role of GRIN2A gene in idiopathic generalized epilepsies and the potential underlying mechanism for phenotypic variation. Methods: Whole-exome sequencing was performed in a cohort of 88 patients with idiopathic generalized epilepsies. Electro-physiological alterations of the recombinant N-methyl-D-aspartate receptors (NMDARs) containing GluN2A mutants were examined using two-electrode voltage-clamp recordings. The alterations of protein expression were detected by immunofluorescence staining and biotinylation. Previous studies reported that epilepsy related GRIN2A missense mutations were reviewed. The correlation among phenotypes, functional alterations, and molecular locations was analyzed. Results: Three novel heterozygous missense GRIN2A mutations (c.1770A > C/p.K590N, c.2636A > G/p.K879R, and c.3199C > T/p.R1067W) were identified in three unrelated cases. Electrophysiological analysis demonstrated R1067W significantly increased the current density of GluN1/GluN2A NMDARs. Immunofluorescence staining indicated GluN2A mutants had abundant distribution in the membrane and cytoplasm. Western blotting showed the ratios of surface and total expression of the three GluN2A-mutants were significantly increased comparing to the wild type. Further analysis on the reported missense mutations demonstrated that mutations with severe gain-of-function were associated with epileptic encephalopathy, while mutations with mild gain of function were associated with mild phenotypes, suggesting a quantitative correlation between gain-of-function and phenotypic severity. The mutations located around transmembrane domains were more frequently associated with severe phenotypes and absence seizure-related mutations were mostly located in carboxyl-terminal domain, suggesting molecular sub-regional effects. Significance: This study revealed GRIN2A gene was potentially a candidate pathogenic gene of idiopathic generalized epilepsies. The functional quantitative correlation and the molecular sub-regional implication of mutations helped in explaining the relatively mild clinical phenotypes and incomplete penetrance associated with GRIN2A variants.